The role of faith and religious diversity in educational practices - DeHart, Jason D. (IGI Global, 2024)
"The neglect of faith and religious diversity within educational practices poses a significant challenge in fostering inclusive learning environments. The current educational landscape often overlooks the profound impact of religion on individuals' identities and beliefs, leading to a lack of understanding and appreciation for diverse faith perspectives. This omission limits the potential for meaningful dialogue and hinders the development of equitable educational spaces.The Role of Faith and Religious Diversity in Educational Practices, edited by Jason DeHart, offers a compelling solution to address this critical issue. This transformative book explores the intersections between faith and educational practices, drawing on research-based narratives and studies to illuminate the implications of policy and practice through a faith-based lens. By embracing a broad definition of religion and faith, it fosters diverse perspectives and encourages critical reflection on the importance of religious diversity in education. Through practical insights and evidence-based guidance, this book empowers researchers and educators to create inclusive spaces for faith-related discussions and develop policies that honor and respect religious identities. By engaging with this book, scholars and educators can take tangible steps toward cultivating inclusive and enriching learning environments that value and celebrate the diverse religious perspectives of all students."--